The International air cargo industry : a modal analysis - Nolan, James; People, James (Emerald Publishing Limited, 2022)
With the growth of just-in-time delivery and e-commerce, fast and efficient cargo delivery remains in high demand around the globe. Not so long ago, the air cargo mode was employed mostly to move higher valued goods. Open international trade, combined with scale/scope economies in air transport and the use of modern commercial jets means that now some formerly "bulky" commodities are moved by air, a modal choice that would have been unthinkable a generation ago. However, as it grows the industry is not without its controversies or detractors. Employing various empirical techniques and modeling perspectives, the authors highlight the methods by which air cargo companies today provide effective and increasingly affordable services and how such services enhance economic growth, trade and development. The chapters cover three broad operational areas: costs and competitiveness, shipper services and air cargo company demand, and international competition and economic development. This volume provides the researcher with an updated "snapshot" of this international industry and provides governments with strong evidence that the development of an internationally competitive air cargo sector will likely continue to generate significant economic benefits across the globe.
Keywords: Aeronautics, Commercial -- Freight.; Transportation -- Aviation / Commercial.; Aerospace & air transport industries.; elektronické knihy; electronic books